The Relation between Microstructure Composition and Fatigue Properties of ADI - Hanzlikova, Klara; Vechet, Stanislav; Kohout, Jan (Communications - Scientific letters of the University of Zilina, 2006)
The presented work deals with a high-strength variant of nodular cast iron, so-called ADI (austempered ductile iron). This material ranks among prospective structural materials and is more and more applied in all important branches of machine industry. Recently it has even been applied to castings for cyclically loaded components, i.e. gears and traversing wheels, crankshafts of motor-cars, vans and trucks, swivel pins, rail brakes, pressure pipes in oil industry etc. The microstructure composition of an ADI matrix consists especially of bainitic ferrite and stabilized austenite. However, in dependence on transformation dwell some amount of martensite can appear as well. In this work the relation between mechanical properties and microstructure composition of the matrix mixture was studied in detail for the case of ADI transformed at 380 °C, with emphasis on fatigue properties.